Pelatihan Peningkatan Self-Esteem pada Mahasiswa Universitas Indonesia yang Mengalami Distres Psikologis - Bona Sardo Hasoloan Hutahaean; Nathanael E. J. Sumampouw (Fakultas Psikologi Universitas Pancasila, 2018)
Undergraduate students with high levels of self-esteem tend to have good adjustments in lectures. They will have the ability to deal with college problems and automatically reduce their psychological distress. This study used a quasi experimental method which is conducted to determine the increase of self-esteem in students who experience psychological distress. Participants of this study were 8 undergraduate students from Universitas Indonesia aged 18-23 years with a level of self-esteem below the value of 29 as measured by Rosenberg self-esteem scale (RSES), and had a level of psychological distress above the value of 1.75 as measured by HSCL-25. Participants were involved in the intervention of increasing self-esteem consisting of 5 main sessions for two consecutive days (about 6 hours a day). Four weeks after the second day of training, the participant's level of self-esteem and psychological distress were measured. The result of pre and posttest intervention showed that the participant’s mean score of self-esteem increased and the mean score of psychological distress decreased. The result of Wilcoxon test also showed a significant change in both variables (Z RSES = -2.246; Z HSCL-25 = -2.366; p < .05). This study shows that training intervention is effective in increasing the level of self-esteem and reducing the level of psychological distress for undergraduate students at Universitas Indonesia. Participants also commented that they gained new knowledge about self-esteem and new skills to communicate assertively and think positively.